Analysis of the average yield per hectare for the main autumn crops and determination of the influencing factors - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
In this paper we will analyze the average yield per hectare for the main field crops, autumn, in order to determine the development regions with a higher potential. It will be analyzed from a statistical point of view whether regions with higher productivity differ significantly from the national average. This analysis will be determined by testing the hypotheses using the t test. Determining the region with the best yield for autumn crops will be analyzed and possible factors that led to this distancing in that region, also with the help of the t test it will be possible to see if certain inputs differed quantitatively in that region from the national average.
Keywords: Q10; Q15; 330; field crops; autumn crops; yield; hypothesis testing; inputs